Mobile computing : securing your workforce. (British Informatics Society, 2011)
According to a recent iPass report, 73% of enterprises allow non-IT managed devices to access company resources. 65% of companies report security issues. This ebook looks at the security risks of an increasingly mobile workforce and proposes a range of possible solutions. Topics include: personal mobile devices at work; passwords; data encryption.